Seven Aspects of Healthcare Customer Satisfaction And Factors Affecting It Within Emergency Department - Muhammad Irfan Irfan; Mirza Kashif Baig (ACHSM, 2023)
Objectives: This study aimed at investigating seven aspects, which are believed to be critical for healthcare customer satisfaction level, as well as determining underlying factors affecting them within the emergency department. Design: A quantitative and cross-sectional study design, with deductive reasoning, was applied to undertake this study. Setting: The study site involves different tertiary care private and public hospitals in Karachi, Pakistan. Main Outcome Measures: General satisfaction perspective was measured involving satisfaction with technical quality, interpersonal manner, communication, financial aspects, time spent with the doctor, and accessibility and convenience. Results: Respondents were 61.6% male and 38.4% female with mean age 34.65±10.27 years. Most of the healthcare customers (54.6%) commuted to the healthcare facility by ambulance. 72.2% of respondents were from private and 27.8% were from public healthcare facilities while the majority (55.4%) visits to healthcare emergency services were due to injury or intoxication. In our study mean general satisfaction, technical quality, interpersonal manner, communication, financial aspects, time spent with the doctor, and accessibility and convenience were 3.11±0.34, 3.42±0.37, 3.42±0.43, 3.45±0.39, 3.31±0.42, 2.80±0.58 and 3.46±0.59 respectively. We found 52.6% of healthcare customers were satisfied with general aspects of service, 81.5% satisfied with technical quality, 80.50% satisfied with interpersonal manner, 82.5% satisfied with the communication, 66.3% satisfied with financial aspects, 20.4% satisfied with time spent with doctors and 75.7% satisfied with accessibility and convenience. Conclusion: General satisfaction with services was found to be at the lowest level, while the highest satisfaction level was with the "time spent with the doctor". Healthcare institutes need to be more attentive to the service encounter time spent with doctors and on general issues for healthcare customers visiting the ED.